A DEFICIÊNCIA INTELECTUAL EM REPRESENTAÇÕES DE PROFESSORES DO ENSINO FUNDAMENTAL - HAAG, Cassiano Ricardo; FRONZA, Cátia de Azevedo (Intercâmbio, 2014)
RESUMO: A partir do contato com professores, serão discutidas representações sobre seus alunos com deficiência intelectual. Serão analisadas entrevistas semiestruturadas, a partir dos tópicos “deficiência” e “aprendizagem”. Os tópicos mencionados podem revelar aspectos importantes das representações construídas por esses profissionais. A revelação do diagnóstico de déficit cognitivo reduz as expectativas de aprendizagem e interfere na qualidade das interações que o sujeito passa a vivenciar. A análise das entrevistas aponta certa tensão entre a adequação a um discurso “politicamente correto”, orientado pela aposta na aprendizagem, por um lado, e a aceitação de um discurso científico que determina um limite cognitivo, por outro. ABSTRACT: Out of the contact with teachers, representations that they have of their students who have intellectual disabilities will be discussed. Semi-structured interviews about the topics "disability" and "learning" will be analyzed. The mentioned topics may reveal important aspects of the representations constructed by these professionals. The disclosure of a diagnosis of cognitive impairment may reduce the learning expectations about the diagnosed subject and interfere with the quality of the interactions that this person starts to experience. The analysis of the interviews indicates some tension between the fitness for a "politically correct" speech, that is guided by the commitment to learning, on the one hand, and the acceptance of a scientific discourse that determines a cognitive limit, on the other.